Silicon-carbon negative electrode material for chemical liquid phase deposition and preparation method and application of silicon-carbon negative electrode material
The chemical liquid deposition method of nanosilicon particles on the porous carbon framework and the carbon source coating layer is covered, which solves the problem of poor electrochemical performance of existing silicon carbon anode materials, and achieves an efficient and environmentally friendly preparation process and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411716841.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-04
AI Technical Summary
The existing silicon-carbon anode materials have poor performance in electrochemical cycle stability, capacity retention rate and Coulomb efficiency. The traditional preparation methods consume a lot of energy, have great safety hazards, and are seriously polluted by the environment, and are not suitable for large-scale industrial production.
The silicon-carbon negative electrode material was prepared by chemical liquid deposition method. Nanosilicon particles were deposited on the porous carbon framework and coated with a carbon source coating to form a composite structure to improve electrochemical performance.
It significantly improves electrochemical cycle stability, capacity retention rate and Coulomb efficiency, and is simple in preparation, low energy consumption, environmentally friendly, suitable for large-scale production.
Smart Images

Figure CN119764366A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a chemical liquid phase deposited silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] At present, chemical vapor deposition (CVD), mechanical ball milling, sol-gel method and other methods are commonly used to prepare silicon-carbon negative electrode materials. Patent CN118676342A prepares carbon-coated silicon-carbon negative electrode materials by carbonization and chemical vapor deposition, and obtains higher initial coulombic efficiency and specific capacity; Patent CN118630194A mixes graphite and nano-silicon by high-energy ball milling, and then planetary ball mills the composite with the coating agent to obtain high-rate and long-cycle silicon-carbon negative electrode materials; Patent CN112072115B uses the sol-gel method to mix silicon dioxide The nano-silicon core is coated, and then the nano-silicon / silicon dioxide microspheres are compounded with a carbon source to obtain a high-energy-density silicon-carbon negative electrode material; Patent CN105655555B obtains porous silicon by subjecting the silicon metal alloy material to two acid corrosions, and then compounds it with carbon and coats it with carbon, thereby enhancing the conductivity and electrochemical properties of silicon; Patent CN118693266A uses a silane cracking method to deposit silicon on porous carbon, and coats heteroatom-doped amorphous carbon on the outermost layer, thereby improving the first coulombic efficiency, cycle stability and rate performance of the negative electrode.
[0003] However, in the existing methods, the mechanical ball milling method consumes a lot of energy and the particles are easy to agglomerate during the preparation process; the chemical vapor deposition method requires high temperature and high vapor pressure conditions, requires a lot of energy and has safety hazards, and will produce toxic and harmful gases and a large amount of waste liquid, polluting the environment. Although patent CN118703981A has designed a low-energy and low-emission chemical vapor deposition scheme, it still requires a relatively complex operating process and is not suitable for large-scale industrial production of silicon-carbon negative electrodes. In addition, the silicon-carbon negative electrode materials obtained by the current preparation method generally still have the problems of poor electrochemical cycle stability, low capacity retention rate and coulomb efficiency.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a chemical liquid phase deposited silicon-carbon negative electrode material and a preparation method and application thereof, aiming to solve the problems of poor electrochemical cycle stability, low capacity retention rate and coulombic efficiency of the existing prepared silicon-carbon negative electrode materials.
[0006] The technical solution of the present invention is as follows:
[0007] A chemical liquid phase deposited silicon-carbon negative electrode material comprises a porous carbon skeleton, nano silicon particles deposited on the surface and in pores of the porous carbon skeleton, and a carbon source coating layer coating the porous carbon skeleton and the nano silicon particles.
[0008] The chemical liquid phase deposited silicon-carbon negative electrode material, wherein the porous carbon skeleton is one of coconut shell-derived porous carbon balls and other biomass-based porous carbon, resin-based porous carbon, and coal-based porous carbon; the material of the carbon source wrapping layer includes one of asphalt-derived carbon materials, organic-derived carbon, sugar-derived carbon, resin-derived carbon, carbon black, graphene, and carbon nanotubes.
[0009] The chemical liquid phase deposited silicon-carbon negative electrode material, wherein the particle size of the nano silicon particles is 10nm-25nm; the thickness of the carbon source coating layer is 5nm-15nm.
[0010] A method for preparing a silicon-carbon negative electrode material based on chemical liquid deposition comprises the following steps:
[0011] Performing hydroxylation on the porous carbon material to obtain a surface hydroxylated porous carbon material;
[0012] The surface hydroxylated porous carbon material is mixed with liquid organosilicon, and subjected to drying treatment to obtain a porous carbon material with deposited (HSiO)2O;
[0013] Mixing the carbon source with the organic solvent to obtain a mixed solution;
[0014] Mixing the deposited (HSiO)2O porous carbon material with the mixed solution to obtain a slurry;
[0015] The slurry is subjected to pyrolysis reduction treatment to obtain a silicon-carbon negative electrode material.
[0016] The method for preparing the chemical liquid phase deposited silicon-carbon negative electrode material, wherein the liquid organic silicon is centered on a silicon atom, and the silicon atom is connected to four functional groups, and the functional groups include one or two of hydrogen or halogen elements; the purity of the liquid organic silicon is 99.0%-99.9%.
[0017] The method for preparing the chemical liquid phase deposited silicon-carbon negative electrode material, wherein the carbon source is heavy oil with different asphaltene contents; the asphaltene content in the heavy oil is 30wt%-50wt%.
[0018] The method for preparing the chemical liquid phase deposited silicon-carbon negative electrode material, wherein the mass ratio of the carbon source to the organic solvent is 1:(1.6-8); the volume ratio of the added amount of the mixed solution to the liquid organic silicon is 1:(1-2).
[0019] The method for preparing the chemical liquid phase deposited silicon-carbon negative electrode material, wherein the method of mixing the deposited (HSiO)2O porous carbon material with the mixed solution is stirring ball milling; the stirring rod speed of the stirring ball milling is 300rmp-600rmp, and the time of the stirring ball milling is 2h-4h.
[0020] The method for preparing the chemical liquid phase deposited silicon-carbon negative electrode material, wherein the pyrolysis reduction treatment is carried out under an inert atmosphere containing hydrogen; the heating rate of the pyrolysis reduction treatment is 5°C / min-10°C / min, the temperature of the pyrolysis reduction treatment is 750°C-900°C, and the time of the pyrolysis reduction treatment is 4h-6h.
[0021] The invention discloses an application of silicon-carbon negative electrode material based on chemical liquid deposition in lithium-ion batteries.
[0022] Beneficial effects: The present invention provides a chemical liquid phase deposited silicon-carbon negative electrode material and its preparation method and application. The chemical liquid phase deposited silicon-carbon negative electrode material includes a porous carbon skeleton, nano-silicon particles deposited on the surface and in the pores of the porous carbon skeleton, and a carbon source coating layer that coats the porous carbon skeleton and the nano-silicon particles. The composite structure of the silicon-carbon negative electrode material provided by the present invention is that the nano-silicon particles are deposited on the surface and in the pores of the porous carbon skeleton, and the outer layer is a coating layer; wherein, the porous carbon as a continuous and stable carbon skeleton can effectively alleviate the volume expansion and particle fragmentation of the silicon-based material, and the outermost coating layer can improve the structural stability and conductivity of the composite material, thereby improving the electrochemical cycle stability; in addition, the structure of the silicon-carbon negative electrode material combines the advantages of the embedded and core-shell structures, which not only provides a carbon skeleton for the silicon-carbon negative electrode material, but also provides a limited expansion space for the silicon particles to prevent crushing, greatly improving the cycle stability of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of a process flow for preparing a silicon-carbon negative electrode material by chemical liquid phase deposition of the present invention;
[0024] Figure 2 This is a SEM characterization image of the silicon-carbon negative electrode material prepared in Example 1;
[0025] Figure 3 This is a graph showing electrochemical test data of a lithium-ion battery made using the silicon-carbon negative electrode material of Example 1. DETAILED DESCRIPTION
[0026] The present invention provides a chemical liquid phase deposited silicon-carbon negative electrode material and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.
[0028] Lithium-ion batteries (LIBs) play a vital role as the most promising new energy storage device; they have been recognized by the market for their many attractive characteristics such as light weight, high energy density, small size, no memory effect, long cycle life and low pollution. Among them, silicon-based negative electrode materials have a much higher specific capacity than graphite (the theoretical capacity of graphite is 372mAh / g, and the theoretical capacity of silicon is 4200mAh / g). Their application can meet the needs of more fields and lead lithium-ion batteries into a new generation of rapid development.
[0029] However, the silicon-based negative electrode will produce a huge volume expansion during the lithiation process, which will lead to the crushing of active materials or even structural collapse, instability and continuous growth of the anode-electrolyte interface (SEI) structure, and continuous consumption of electrolyte. Therefore, many inventors have improved the performance of silicon-based materials through structural design and composite materials. Among them, silicon-carbon composite negative electrodes including embedded, core-shell, yolk-shell and other structures can effectively alleviate the expansion of silicon particles and prevent particle crushing. It combines the high specific capacity of silicon and the excellent stability of carbon, and effectively improves electrochemical properties such as stability and first coulomb efficiency (ICE). However, the silicon-carbon negative electrode materials obtained by the current preparation method still have the problems of poor electrochemical cycle stability, low capacity retention rate and coulomb efficiency.
[0030] Based on this, the present invention provides a chemical liquid phase deposited silicon-carbon negative electrode material, comprising a porous carbon skeleton, nano-silicon particles deposited on the surface and in the pores of the porous carbon skeleton, and a carbon source coating layer that coats the porous carbon skeleton and the nano-silicon particles.
[0031] In this embodiment, the composite structure of the silicon-carbon negative electrode material is composed of nano-silicon particles deposited on the surface and pores of a porous carbon skeleton, and the outer layer is a carbon source coating layer; wherein, the porous carbon as a continuous and stable carbon skeleton can effectively alleviate the volume expansion and particle fragmentation of the silicon-based material, and the outermost coating layer can improve the structural stability and conductivity of the composite material, thereby improving the electrochemical cycle stability; in addition, the structure of the silicon-carbon negative electrode material combines the advantages of the embedded and shell-core structures, which not only provides a stable carbon skeleton for the silicon-carbon negative electrode material, but also provides a limited expansion space for the silicon particles to prevent crushing, greatly improving the cycle stability of the negative electrode material. Moreover, the capacity retention rate of the silicon-carbon negative electrode material after 450 cycles under 0.2C conditions is above 94%, and the coulombic efficiency is always maintained above 99.8%.
[0032] In some embodiments, the porous carbon skeleton is but not limited to coconut shell-derived porous carbon balls (PAC-70) and other biomass-based porous carbons, resin-based porous carbons, and coal-based porous carbons; further, the porous carbon skeleton can be any carbon with a porous structure, which can achieve the effect of electrochemical cycle stability of silicon-carbon negative electrode materials; the carbon source coating layer includes but is not limited to one of asphalt-derived carbon materials, organic-derived carbon, sugar-derived carbon, resin-derived carbon, carbon black, graphene, and carbon nanotubes.
[0033] In some embodiments, the particle size of the nano silicon particles is 10nm-25nm; the thickness of the carbon source coating layer is 5nm-15nm. Controlling the particle size of the nano silicon particles within the above range can prevent the silicon nano particles from breaking when expanding in the limited pores of the porous carbon skeleton, and the coating layer thickness within the above range can improve the structural stability and conductivity of the composite material, thereby improving the electrochemical cycle stability.
[0034] In addition, Figure 1 As shown, the present invention also provides a method for preparing a silicon-carbon negative electrode material based on chemical liquid deposition, comprising the steps of:
[0035] Step S10: performing hydroxylation treatment on the porous carbon material to obtain a porous carbon material with surface hydroxylation;
[0036] Step S20: mixing the surface hydroxylated porous carbon material with liquid organic silicon, and drying the mixture to obtain a porous carbon material with deposited (HSiO)2O;
[0037] Step S30: mixing the carbon source and the organic solvent to obtain a mixed solution;
[0038] Step S40: mixing the deposited (HSiO)2O porous carbon material with the mixed solution to obtain a slurry;
[0039] Step S50: performing pyrolysis reduction treatment on the slurry to obtain a silicon-carbon negative electrode material.
[0040] In this embodiment, (HSiO)2O is obtained from liquid organic silicon by hydrolysis of organic silicon through chemical liquid deposition and deposited on a porous carbon material, and then mixed with a mixed solution, and then pyrolysis reduction treatment is performed to finally obtain a silicon-carbon negative electrode material with a composite structure. In addition, the composite structure of the silicon-carbon negative electrode material prepared by the preparation method is nano-silicon particles deposited on the surface and pores of the porous carbon skeleton, and the outer layer is a coating layer; wherein, porous carbon as a continuous and stable carbon skeleton can effectively alleviate the volume expansion and particle fragmentation of silicon-based materials, and the outermost coating layer can improve the structural stability and conductivity of the composite material, thereby improving the electrochemical cycle stability. Moreover, the preparation method can adjust the relative content of silicon and carbon to obtain silicon-carbon negative electrode materials with different target capacities to meet different application scenarios. In addition, the preparation process of the present invention using liquid phase deposition to prepare silicon-carbon negative electrode materials is simple, the equipment requirements are low, high temperature and vacuum state are not required, and no toxic and harmful gases and a large amount of waste liquid are generated during the preparation process, which provides a new idea for the large-scale environmentally friendly production of silicon-carbon composite materials.
[0041] Specifically, the chemical liquid phase deposition method of the present invention can effectively utilize the silicon source in the organic solvent, deposit silicon on the porous carbon surface and in the pores in the liquid phase, then add a carbon coating layer, and obtain a silicon-carbon negative electrode material with a composite structure through pyrolysis and reduction. Compared with traditional vapor deposition, the silicon-carbon negative electrode material prepared by the preparation method of the present invention can improve the deposition uniformity of silicon, providing a basis for the large-scale production and industrialization of silicon-carbon negative electrode materials.
[0042] In some embodiments, the liquid organosilicon is centered on a silicon atom, and four functional groups are connected to the silicon atom, and the functional groups include one or two of hydrogen or halogen elements; the purity of the liquid organosilicon is 99.0%-99.9%. Controlling the purity between 99.0%-99.9% can increase the silicon content in the organosilicon and reduce impurities, avoiding affecting the electrochemical performance of the silicon-carbon negative electrode material.
[0043] In a preferred embodiment, the silicon source in the liquid organic silicon is trichlorosilane, and the purity of the trichlorosilane is 99.9%.
[0044] In some embodiments, the organic solvent is but not limited to toluene.
[0045] In some embodiments, the carbon source is heavy oil with different asphaltene contents; the asphaltene content in the heavy oil is 30wt%-50wt%. The use of heavy oil with an asphaltene content between 30wt% and 50wt% can play a coating role, prevent the loss of silicon during the pyrolysis process, and also improve the cycle stability of the negative electrode material.
[0046] In some embodiments, the mass ratio of the carbon source to the organic solvent is 1:(1.6-8); the volume ratio of the mixed solution to the liquid organic is 1:(1-2). Within this ratio range, the carbon source can coat the porous carbon skeleton and nano-silicon particles, preventing the loss of silicon during the pyrolysis process, and also improving the cycle stability of the negative electrode material.
[0047] In a preferred embodiment, the mass ratio of the carbon source to the organic solvent is 2:7; and the volume ratio of the added amount of the mixed solution to the liquid organosilicon is 1:1.
[0048] In some embodiments, in step S10, the hydroxylation treatment of the porous carbon material is specifically: subjecting the porous carbon material to water vapor treatment; the water vapor is vapor droplets generated when pure water reaches the boiling point.
[0049] In some embodiments, the volume of the liquid silicone is 2-5 ml, and the mass of the surface hydroxylated porous carbon material is 400-600 mg, so that (HSiO)2O is uniformly deposited on the surface and in the pores of the surface hydroxylated porous carbon material.
[0050] In some embodiments, the drying temperature is 55°C-70°C, and the drying time is 10-15 hours.
[0051] Specifically, the step S20 specifically includes: in a fume hood, pouring 3 ml of trichlorosilane organic solution into a tetrafluoroethylene bottle, adding 500 mg of the surface hydroxylated porous carbon, standing for 6-8 hours until the liquid completely disappears, and drying the solid residue under vacuum conditions at 60° C. for 12 hours to obtain a porous carbon material deposited with (HSiO)2O. The silicon-carbon negative electrode material obtained in this way can have excellent cycle stability, because silicon is deposited in the porous carbon skeleton, which can limit the volume expansion of silicon and prevent pulverization.
[0052] The reaction principle chemical equation used in step S20 is as follows:
[0053] 2SiHCl3+3H2O→(HSiO)2O+6HCl
[0054] In some embodiments, the porous carbon material deposited with (HSiO)2O is mixed with the mixed solution by stirring ball milling; the stirring rod speed of the stirring ball milling is 300-600 rpm, and the stirring ball milling time is 2-4 hours. The stirring ball milling process is used to disperse the porous carbon material uniformly and allow the carbon source to fully coat the porous carbon surface deposited with silicon.
[0055] Specifically, the step S30 and the step S40 specifically include: mixing 0.6 g of the carbon source with 3 ml of the organic solvent, ultrasonicating for 30 min until there is no solid in the solution to obtain a mixed solution; adding the deposited (HSiO)2O porous carbon material to the mixed solution and stirring and ball milling, the stirring rod speed is 500 rpm, and the treatment time is 3 h; the stirring and ball milling treatment step is carried out under atmospheric environment.
[0056] In some embodiments, the pyrolysis reduction treatment is performed under an inert atmosphere containing hydrogen; the heating rate of the pyrolysis reduction treatment is 5°C / min-10°C / min, the temperature of the pyrolysis reduction treatment is 750°C-900°C, and the time of the pyrolysis reduction treatment is 4h-6h. The pyrolysis reduction treatment of the slurry under the pyrolysis reduction treatment parameters can decompose the (HSiO)2O on the surface of the deposited porous carbon material and in the pores to generate SiO2 and reduce it to Si, thereby obtaining a silicon-carbon negative electrode material.
[0057] Specifically, the reaction principle chemical equation of the pyrolysis reduction treatment in step S30 is as follows:
[0058] (HSiO)2O=SiO2+H2O;
[0059] At high temperature, SiO2+2H2→Si+2H2O occurs.
[0060] In a preferred embodiment, the heating rate of the pyrolysis reduction treatment is 7°C / min, the temperature of the pyrolysis reduction treatment is 800°C, and the time of the pyrolysis reduction treatment is 5 hours.
[0061] In addition, the present invention also provides an application of a silicon-carbon negative electrode material based on chemical liquid phase deposition in a lithium ion battery.
[0062] In this embodiment, the structure of the silicon-carbon negative electrode material combines the advantages of the embedded and core-shell structures, providing a carbon skeleton for the silicon-carbon negative electrode material and a limited expansion space for the silicon particles to prevent crushing, thereby greatly improving the cycle stability of the negative electrode material. When the silicon-carbon negative electrode material is used in a lithium-ion battery, the capacity retention rate is above 94% after 450 cycles at 0.2C, and the coulombic efficiency is always maintained above 99.8%.
[0063] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.
[0064] Example 1
[0065] This embodiment provides a chemical liquid phase deposited silicon-carbon negative electrode material, and the preparation steps thereof include the following:
[0066] Step 1: Take 500 mg of coconut shell-derived porous carbon material and treat it with water vapor to obtain a surface hydroxylated porous carbon material;
[0067] Step 2: Immerse the surface hydroxylated porous carbon material in a tetrafluoroethylene bottle containing 3 ml of trichlorosilane and let it stand until the liquid disappears completely, then dry the solid residue under vacuum at 60° C. for 12 h to obtain a porous carbon material deposited with (HSiO)2O;
[0068] Step 3: 0.6 g of asphalt with an asphaltene content of 47% was dissolved in 3 ml of toluene to obtain an asphalt solution;
[0069] Step 4: adding the deposited (HSiO)2O porous carbon material to the asphalt solution and subjecting it to stirring ball milling for 3 hours to obtain a slurry;
[0070] Step 5: Place the slurry in a tubular furnace for pyrolysis reduction treatment. In an atmosphere of N2-H2 mixed gas, the heating rate is 7°C / min and the temperature is kept at 800°C for 5 hours to finally obtain a chemical liquid phase deposited silicon-carbon negative electrode material.
[0071] The microstructure of the silicon-carbon negative electrode material prepared in this embodiment is characterized, and its SEM image is as follows: Figure 2 The electrochemical performance of the silicon-carbon negative electrode material prepared in this embodiment was tested, and the test results are shown in Figure 3 As shown, the capacity retention rate is 94% after 450 cycles at 0.2C, and the first coulombic efficiency is 89.9%. After three cycles, the coulombic efficiency remains above 99.8%.
[0072] In summary, the present invention provides a chemical liquid phase deposited silicon-carbon negative electrode material and its preparation method and application. The chemical liquid phase deposited silicon-carbon negative electrode material includes a porous carbon skeleton, nano-silicon particles deposited on the surface and pores of the porous carbon skeleton, and a coating layer that coats the porous carbon skeleton and the nano-silicon particles. The composite structure of the silicon-carbon negative electrode material provided by the present invention is that the nano-silicon particles are deposited on the surface and pores of the porous carbon skeleton, and the outer layer is a coating layer; wherein, the porous carbon as a continuous and stable carbon skeleton can effectively alleviate the volume expansion and particle fragmentation of the silicon-based material, and the outermost coating layer can improve the structural stability and conductivity of the composite material, thereby improving the electrochemical cycle stability; in addition, the structure of the silicon-carbon negative electrode material combines the advantages of the embedded and core-shell structures, which not only provides a carbon skeleton for the silicon-carbon negative electrode material, but also provides a limited expansion space for the silicon particles to prevent crushing, greatly improving the cycle stability of the negative electrode material.
[0073] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A chemical liquid phase deposited silicon-carbon negative electrode material, characterized in that: The invention comprises a porous carbon skeleton, nano silicon particles deposited on the surface and in the pores of the porous carbon skeleton, and a carbon source coating layer for coating the porous carbon skeleton and the nano silicon particles.
2. The chemical liquid phase deposited silicon-carbon negative electrode material according to claim 1, characterized in that: The porous carbon skeleton is one of coconut shell-derived porous carbon balls and other biomass-based porous carbon, resin-based porous carbon, and coal-based porous carbon; the material of the carbon source wrapping layer includes one of asphalt-derived carbon materials, organic-derived carbon, sugar-derived carbon, resin-derived carbon, carbon black, graphene, and carbon nanotubes.
3. The chemical liquid phase deposited silicon-carbon negative electrode material according to claim 1, characterized in that: The particle size of the nano silicon particles is 10nm-25nm; the thickness of the carbon source coating layer is 5nm-15nm.
4. A method for preparing a silicon-carbon negative electrode material based on chemical liquid deposition as claimed in any one of claims 1 to 3, characterized in that: Includes steps: Performing hydroxylation on the porous carbon material to obtain a surface hydroxylated porous carbon material; The surface hydroxylated porous carbon material is mixed with liquid organosilicon, and subjected to drying treatment to obtain a porous carbon material with deposited (HSiO)2O; Mixing the carbon source with the organic solvent to obtain a mixed solution; Mixing the deposited (HSiO)2O porous carbon material with the mixed solution to obtain a slurry; The slurry is subjected to pyrolysis reduction treatment to obtain a silicon-carbon negative electrode material.
5. The method for preparing a silicon-carbon negative electrode material by chemical liquid deposition according to claim 4, characterized in that: The liquid organic silicon has a silicon atom at its center and four functional groups connected to the silicon atom. The functional groups include one or two of hydrogen or halogen elements. The purity of the liquid organic silicon is 99%-99.9%.
6. The method for preparing a silicon-carbon negative electrode material by chemical liquid deposition according to claim 4, characterized in that: The carbon source is heavy oil with different asphaltene contents; the asphaltene content in the heavy oil is 30wt%-50wt%.
7. The method for preparing a silicon-carbon negative electrode material by chemical liquid deposition according to claim 4, characterized in that: The mass ratio of the carbon source to the organic solvent is 1:(1.6-8); the volume ratio of the added amount of the mixed solution to the liquid organic silicon is 1:(1-2).
8. The method for preparing a silicon-carbon negative electrode material by chemical liquid deposition according to claim 4, characterized in that: The method of mixing the deposited (HSiO)2O porous carbon material with the mixed solution is stirring ball milling; the stirring rod speed of the stirring ball milling is 300rmp-600rmp, and the stirring ball milling time is 2h-4h.
9. The method for preparing a silicon-carbon negative electrode material by chemical liquid deposition according to claim 4, characterized in that: The pyrolysis reduction treatment is carried out in an inert atmosphere containing hydrogen; the heating rate of the pyrolysis reduction treatment is 5°C / min-10°C / min, the temperature of the pyrolysis reduction treatment is 750°C-900°C, and the time of the pyrolysis reduction treatment is 4h-6h.
10. Application of the silicon-carbon negative electrode material based on chemical liquid deposition as claimed in any one of claims 1 to 3 in a lithium-ion battery.
Citation Information
Patent Citations
A silicon-carbon composite material, its preparation method and its application
CN105655555B
Cited By
Preparation method of porous carbon-silicon composite negative electrode material of lithium battery and lithium battery
CN120432517A
Silicon-carbon negative electrode material based on conductive carbon skeleton and preparation method of silicon-carbon negative electrode material
CN120637470A
Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and battery
CN120749157A
Dual-scale nanometer silicon battery negative electrode material and preparation method and application thereof
CN120774408A
A dual-scale nano-silicon solar cell anode material, its preparation method, and its application.
CN120774408B